RELATION BETWEEN EMOTIONAL INTELLIGENCE AND REASONING ABILITY OF HIGHER SECONDARY STUDENTS - Nambikkai, Daisy; Veliappan, A. (International Journal of Research -GRANTHAALAYAH, 2016)
The present study aims to find out the relationship between emotional intelligence and reasoning ability of the higher secondary students. Among the population, 724 samples of higher secondary students were selected randomly from Puducherry region. Findings of the study were i) significant difference is found between male and female higher secondary students in their reasoning ability in science on analogical reasoning, classification as reasoning, eclectic reasoning, deductive reasoning and inductive reasoning.ii) Significant difference is found between male and female higher secondary students in their emotional intelligence on intrapersonal awareness. iii) Significant difference is found among government, aided and unaided schools of higher secondary students in their reasoning ability in science on classification as reasoning and eclectic reasoning. iv) Significant difference is found among government, aided and unaided schools of higher secondary students in their emotional intelligence on intrapersonal awareness, interpersonal awareness, intrapersonal management and interpersonal management. v) there exists significant positive relationship between reasoning ability in science and emotional intelligence of higher secondary students.